Insights to the HIV-associated visceral leishmaniasis clinical outcome: lessons learned about immune mediated disorders - Silva-Freitas, Maria Luciana; Corrêa-Castro, Gabriela; Da-Cruz, Alda Maria; Santos-Oliveira, Joanna Reis (Frontiers in Immunology, 2025)
Most cases of visceral leishmaniasis (VL) and human immunodeficiency virus (HIV) co-infection (VL/HIV) in the Americas occur in Brazil, and the prevalence of VL/HIV has been increasing since 2019, reaching 19% in 2023. This association presents a challenge for the management of VL, since both VL and HIV infection share immunopathogenic characteristics that can reciprocally affect co-infected patients. Thus, VL may contribute to the immunosuppression and other immunological disturbances associated with the rapid progression to acquired immunodeficiency syndrome (AIDS), whereas HIV infection accelerates the development of active VL and reduces the probability of a successful response to anti-Leishmania therapy, resulting in an increase in the relapse and lethality rates of VL. In this synergistic impairment, one of the most critical hallmarks of VL/HIV co-infection is the enhancement of immunosuppression and intense chronic immune activation, caused not only by each infection per se, but also by the cytokine storm and translocation of microbial products. Thus, co-infected patients present with an impaired effector immune response that may result in inefficient parasitic control. In addition, the chronic activation environment in VL/HIV patients may favor progression to early immunosenescence and exhaustion, worsening the patients’ clinical condition and increasing the frequency of disease relapse. Herein, we review the immunological parameters associated with the immunopathogenesis of VL/HIV co-infection that could serve as good biomarkers of clinical prognosis in terms of relapse and severity of VL.